ABSTRACT METHODS TO CLASSIFY THE STRUCTURE OF WOOD - Bardarov, Nikolai; Todorov, Vladislav; Pancheva, Tanya (Innovation in Woodworking Industry and Engineering design, 2022)
The construction of wood can be represented by both quantitative and qualitative characteristics. Each anatomical element has quantitative indicators. These are the size of the cell gap (lumen), the thickness of the cell wall, the diameter and the length of the cell. The arrangement of these cells relative to each other is very characteristic of each species and varies relatively slightly. It is a qualitative characteristic that can also be represented by quantitative methods. Although the structure of wood varies under the influence of environmental conditions and location in the stem, the most characteristic structures remain relatively constant.The article considers the possibility of using a formal-analytical description of the wood structure, applying abstract measurement methods. The obtained data are identical and can be processed by different mathematical methods. The proposed abstract methods give different classifications of the wood structure. Thus, a tree species in one method falls into one group with some species, in another – with others.